2021
DOI: 10.1111/jfb.14887
|View full text |Cite
|
Sign up to set email alerts
|

Effects of passive integrated transponder tags on short‐term feeding patterns in European perch (Perca fluviatilis)

Abstract: We tested the feeding behaviour of small European perch (Perca fluviatilis) in a laboratory study during the first 24 h after handling and 23 mm passive integrated transponder (PIT) tag implantation. Feeding commenced almost immediately following tagging and overall feeding patterns were unaffected by tagging. However, untagged perch had more feeding events than PIT‐tagged individuals. This discrepancy could be attributed to post‐tagging effects or/and reduced room for food due to the presence of the tag in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
1
1
Order By: Relevance
“…Nonetheless, in the case of such low growth as seen here, a comparison of growth is not a very good indicator of sublethal tagging effects. Some studies have indicated that a reduced feeding/growth may be caused by the simple fact that an implanted object takes up a significant part of the body cavity, thus reducing appetite (Chrysafi et al, 2021), but the data here show no difference in growth between tagged and control fish.…”
contrasting
confidence: 80%
“…Nonetheless, in the case of such low growth as seen here, a comparison of growth is not a very good indicator of sublethal tagging effects. Some studies have indicated that a reduced feeding/growth may be caused by the simple fact that an implanted object takes up a significant part of the body cavity, thus reducing appetite (Chrysafi et al, 2021), but the data here show no difference in growth between tagged and control fish.…”
contrasting
confidence: 80%
“…The tagging procedure may affect fish behaviour in the first days after tagging [ 52 ], and newly tagged fish in the current year would bias the distribution of breeding fish due to the cumulative effect of tagging during season. Therefore, only fish tagged in previous breeding seasons were considered in the analysis of a given year.…”
Section: Methodsmentioning
confidence: 99%